Linguistic-Cognitive And Semantic Features Of Effective Constructions Of English And Uzbek Languages - Davlatova Muhayyo Hasanovna (International Journal of Advanced Science and Technology, 2020)
This article presents centers around verbs able of presenting and or going with the coordinate discourse in English and Russian. The examination displayed incorporates primarily non-speech verbs which in any case tend to present the coordinate discourse in literary works of these societies. The classes of verbs uncovered in both dialects permit to compare and to differentiate their semantics, recurrence of event and utilitarian esteem. The classification proposed within the paper illustrates a few essential similitudes as well as contrasts between English and Russian which in turn may moreover reflect certain ethno-linguistic idiosyncrasies between the two societies.